2009
DOI: 10.3983/twc.2009.0118
|View full text |Cite
|
Sign up to set email alerts
|

Sites of participation: Wiki fandom and the case of Lostpedia

Abstract: This essay explores the award-winning fan site Lostpedia to examine how the wiki platform enables fan engagement, structures participation, and distinguishes between various forms of content, including canon, fanon, and parody. I write as a participant-observer, with extensive experience as a Lostpedia reader and editor. The article uses the "digital breadcrumbs" of wikis to trace the history of fan creativity, participation, game play, and debates within a shared site of community fan engagement. Using the Lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 0 publications
1
29
0
2
Order By: Relevance
“…Though the conclusion of this article forcefully suggests that the transformative textual practices of predominantly female fans are in no way foreclosed by transmedia franchising logics, it is nonetheless significant that this narrative model valorizes and validates historically male-dominated fan practices, and in turn imagines male fans as the primary audience for its content. This gendered valuation of transmedia fan engagement is borne out in one of Mittell's (2009) earlier studies of forensic fandom, an examination of the fan wiki Lostpedia, for the ABC television series Lost (2004)(2005)(2006)(2007)(2008)(2009)(2010). Mittell (2009) found that, precisely because of the television series' growing network of transmedia tie-ins and emphasis on information collection and canonical mastery, any fannish or non-canonical content, so-called "cruft," was deleted from pages on the fan wiki (e.g.…”
Section: Modeling Transmedia Franchising and Fandom In The Mcumentioning
confidence: 99%
See 1 more Smart Citation
“…Though the conclusion of this article forcefully suggests that the transformative textual practices of predominantly female fans are in no way foreclosed by transmedia franchising logics, it is nonetheless significant that this narrative model valorizes and validates historically male-dominated fan practices, and in turn imagines male fans as the primary audience for its content. This gendered valuation of transmedia fan engagement is borne out in one of Mittell's (2009) earlier studies of forensic fandom, an examination of the fan wiki Lostpedia, for the ABC television series Lost (2004)(2005)(2006)(2007)(2008)(2009)(2010). Mittell (2009) found that, precisely because of the television series' growing network of transmedia tie-ins and emphasis on information collection and canonical mastery, any fannish or non-canonical content, so-called "cruft," was deleted from pages on the fan wiki (e.g.…”
Section: Modeling Transmedia Franchising and Fandom In The Mcumentioning
confidence: 99%
“…This gendered valuation of transmedia fan engagement is borne out in one of Mittell's (2009) earlier studies of forensic fandom, an examination of the fan wiki Lostpedia, for the ABC television series Lost (2004)(2005)(2006)(2007)(2008)(2009)(2010). Mittell (2009) found that, precisely because of the television series' growing network of transmedia tie-ins and emphasis on information collection and canonical mastery, any fannish or non-canonical content, so-called "cruft," was deleted from pages on the fan wiki (e.g. the "Pairings" page went from documenting canonical couplings as well as fan ships 2 to just the former).…”
Section: Modeling Transmedia Franchising and Fandom In The Mcumentioning
confidence: 99%
“…As shown by Toton (2008), these modes of knowledge are of different priority in different fan wikisthe result of a communal selection process where aspects or issues are deemed to be of varying degrees of relevance. In a study of a wiki dedicated to the Lost television series, Mittell (2009) outlines how the encyclopedic ambitions of Wikipedia and the established tropes of fan culture are major influences on how principles of selection and priority have developed on the site. Fan wikis are here approached not solely as places of reference, but rather as important sites of participatory fandom whose contents and structures to a significant extent can be read as dynamic representations of the viewpoints and priorities of the communities that create them (Bullard, 2013;Newman, 2011).…”
Section: Player-authored Online Information Resourcesmentioning
confidence: 99%
“…When Ward Cunningham developed the first instantiation of wiki technology in the mid 90s, his stated aim was to create " [t]he simplest online database that could possibly work" (Cunningham and Leuf, 2002). Whereas the basic functionalities of current wiki platforms are described in largely similar terms, research has shown that wiki-based knowledge production is considerably more regulated and ritualized than the open-ended characterization of the wiki as a collaborative content management system seems to necessitate (e.g., Jemielniak, 2014;Mittell, 2009;Reagle, 2010;Sundin, 2011;Toton, 2008). The apparent discrepancy between the modularity with which the wiki platform has become synonymous, and the distinctly regimented ways in which knowledge is produced on Wikipedia and other wikis may be explained by insights attained in the sociocultural study of knowledge [1], where knowledge production is colloquially viewed as bounded and particular (Becher, 1989;Knorr-Cetina, 1999;Latour and Woolgar, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…10 Les sites que nous avons étudiés se divisent d'abord entre ceux centrés sur une série (et dans ce cas liés à un fan-club plus ou moins vaste et structuré) et ceux consacrés au genre dans son ensemble. Les deux suivent des fins diverses : du site internet aux ambitions encyclopédiques visant à recenser tout ce qui se rapporte à cet univers(Mittell, 2009 : à propos du site Lostpedia) jusqu'au forum de discussion, en passant par la formule plus personnalisée et littéraire du blog. Dans la réalité, bien qu'une dominante apparaisse au sein de chaque plateforme, ces différents aspects s'y trouvent peu ou prou conjugués.…”
unclassified